PENDUGAAN PATAHAN DAERAH “Y” BERDASARKAN ANOMALI GAYABERAT DENGAN ANALISIS DERIVATIVE - Yasrifa Fitri Aufia; Karyanto Karyanto; Rustadi Rustadi (Jurnal Geofisika Eksplorasi, 2019)
The research area "Y" is an area of gold mineralization with low sulfidation epithermal type deposit. The existence of this type of mineralization on the path marked by the presence of mineral deposits, which form the quartz veined below the surface of the deposited within the structure of the fault. In this study, analysis of gravity data using derivatives analysis, i.e. First Horizontal Derivative (FHD) to determine the boundary fault structure and Second Vertical Derivative (SVD) to determine the type of fault. The existence of the fault structure integrated with subsurface modeling results in two-dimensional and three-dimensional. The results showed three line slice made in the area of research, identified structure of down faults (normal) trending northeast - south on slice 1 with an estimated dip (slope) is 22° and expected of strike on this fault is N 158° W and thrust fault structure trending northwest - south on slice 2 also slice 3 with an estimated dip (slope) is 22° and expected of strike on this fault is N 158° E. The results of the modeling of two-dimensional and three-dimensional show fracture structure is at the density of 2 g/cc – 2,67 g/cc in the depth of around 100 m - 250 m that consists of sedimentary rocks (clay and sandstone) with a density of 2,2 g/cc – 2,3 g/cc at the age of Tertiary Pliocene, tuff rock with a density of 2,4 g/cc – 2,5 g/cc at the age of Early Miocene and bedrock (basement) in andesite form with a density of 2,67 g/cc.